High-strength anti-halation photoelectric glass material and its preparation method and application

By using specific glass compositions and high-temperature reduction treatment in anti-halo photoelectric glass to form a light absorbing layer, combined with chemical strengthening technology, the existing anti-halo photoelectric glass has been solved, and the multi-faceted performance improvement of glass materials has been achieved to meet the needs of high-end photoelectric detection and precision optics.

CN118164672BActive Publication Date: 2025-03-07CNBM PHOTONICS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410409304.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-07
Publication Date
2025-03-07
Estimated Expiration
2044-04-07

AI Technical Summary

Technical Problem

The existing anti-halo photoelectric glass still has insufficient performance and reliability in application scenarios that meet high performance and high reliability requirements, especially in the fields of low light night vision, ultraviolet detection, space measurement and control, information display, industrial cameras and high-end lenses.

Method used

A glass composition is adopted, which contains 68-75% SiO2, 0.5-1% Bi2O3, 0-5% Li2O, 8-15% Na2O3, 0-6% B2O3, 10-15% Al2O3, 0.1-3% CaO, 0-1% CeO2 and 0.1-1% As2O3, and a light absorption layer is formed by high-temperature reduction treatment, and combined with chemical strengthening technology, the optical performance, mechanical strength and environmental adaptability of the glass are improved.

Benefits of technology

It has achieved significant improvements in spectral transmittance, anti-blocking performance, anti-cross talk, baking temperature, bending intensity and impact resistance of glass materials, meeting the strict requirements in the fields of high-end photoelectric detection and precision optics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118164672B_ABST
    Figure CN118164672B_ABST
Patent Text Reader

Abstract

The present application provides a high-strength anti-halo photoelectric glass and a preparation method and application thereof. The composition of the high-strength anti-halo photoelectric glass, by mass percentage, comprises 68-75% SiO2, 0.5-1% Bi2O3, 0-5% Li2O, 8-15% Na2O, 0-6% B2O3, 10-15% Al2O3, 0.1-3% CaO, 0-1% CeO2 and 0.1-1% As2O3. The high-strength anti-halo photoelectric glass has a wide spectral range, excellent spectral transmittance, high baking temperature resistance, strong bending strength and impact resistance, and can be used to prepare optical input windows of optical systems and photoelectric detection systems. It has broad application prospects in photoelectric detection and precision optics fields such as low-light night vision, ultraviolet detection, space measurement and control, information display, industrial cameras, and high-end lenses.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of glass technology, and in particular to a high-strength anti-halation photoelectric glass material and a preparation method and application thereof. Background Art

[0002] Any discussion of the prior art throughout the specification should not be considered as an admission that such prior art is widely known or forms part of the common general knowledge in the field.

[0003] Anti-halation photoelectric glass is a new type of special glass with the function of eliminating stray light from the base, which makes it very important to use it as an optical input window in optical systems and photoelectric detection systems. The performance and reliability of this glass are directly related to the performance and life of the entire system. In the past few years, with the rapid development of low-light night vision, ultraviolet detection, space measurement and control, information display, industrial cameras and high-end lenses, the requirements for anti-halation photoelectric glass have become increasingly higher, which not only includes its spectral range and stray light absorption rate, but also involves effective area transmittance, baking temperature resistance, and resistance to impact, drop and bending.

[0004] In order to meet these increasingly high requirements, chemical strengthening technology is applied to the production of anti-halation photoelectric glass. This technology can effectively reduce the length and depth of microcracks on the glass surface, and sometimes even completely eliminate smaller microcracks. By forming a layer of compressive stress on the glass surface, the mechanical strength of the glass is enhanced. When external tensile stress acts on the glass surface, this layer of compressive stress must first be offset before damage to the glass can be caused. This strengthening method enables anti-halation photoelectric glass to better meet the needs of serving as an optical input window for optical systems and photoelectric detection systems.

[0005] Despite this, this high-strength anti-halation photoelectric glass will remain an extremely critical core material in key equipment and high-tech fields at present and in the future. Although it has been widely regarded as a backbone material, especially in military applications, there is still a clear gap between domestic products and the international advanced level. This gap is mainly reflected in the comprehensive performance and reliability of material properties, especially in application scenarios that meet high performance and high reliability requirements. Current technologies and materials cannot fully meet the demand for high-performance anti-halation photoelectric glass in fields such as low-light night vision, ultraviolet detection, space measurement and control, information display, industrial cameras and high-end lenses.

[0006] Faced with this situation, the development and manufacture of more advanced anti-halation photoelectric glass has become an urgent need. This requires in-depth research on the structure and properties of the material itself in order to further improve the performance and better serve various high-end photoelectric detection and precision optics fields.

[0007] The purpose of the present invention is to overcome or improve at least one disadvantage of the prior art, or to provide a useful alternative. Unless the context clearly requires otherwise, throughout the specification and claims, the words "include", "comprises", etc. should be interpreted from an inclusive perspective rather than an exclusive or exhaustive perspective; that is, from the perspective of "including, but not limited to". Summary of the invention

[0008] Therefore, the purpose of this application is to provide an anti-halation photoelectric glass with higher performance and reliability, so as to achieve a comprehensive improvement in optical performance, mechanical strength and environmental adaptability, and meet the stringent requirements of high-end photoelectric detection and precision optics. Specifically, the present invention provides a glass composition, a glass material prepared from the glass composition, and in particular a high-strength anti-halation photoelectric glass, as well as a preparation method and the application of these glass materials in the field of photoelectric detection and precision optics.

[0009] Specifically, the present invention provides the following technical features, and the combination of one or more of the following technical features constitutes the technical solution of the present invention.

[0010] In a first aspect of the present invention, a glass composition is provided, which comprises or consists of the following components, in mass percentage: 68-75% SiO2, 0.5-1% Bi2O3, 0-5% Li2O, 8-15% Na2O, 0-6% B2O3, 10-15% Al2O3, 0.1-3% CaO, 0-1% CeO2 and 0.1-1% As2O3.

[0011] The basic composition of the glass composition of the present invention must contain specific contents of SiO2, Bi2O3, Na2O, Al2O3, CaO and As2O3, and optionally contain B2O3, Li2O and CeO2, which makes the glass material having the glass composition of the present invention have excellent spectral transmittance, excellent stray light elimination and anti-crosstalk performance, higher baking temperature resistance, higher bending strength, better impact resistance, drop resistance and other properties, and can have good process adaptability during processing, physical and chemical reduction and chemical strengthening.

[0012] In the present invention, SiO2, as a glass former oxide, is the main component of the glass skeleton network structure and exists in the glass structure in the form of [SiO4] tetrahedron. SiO2 plays a role in reducing the thermal expansion coefficient in glass and improving the thermal stability, heat resistance, chemical stability, and mechanical strength of glass. In an embodiment of the present invention, the content of SiO2 is 68-75% by mass percentage. In some embodiments of the present invention, the content of SiO2 is 68-69%, 68-71%, 68-72%, 68-72.3%, 68-75%, 69-71%, 69-72%, 69-72.3%, 69-75%, 71-72%, 71-72.3%, 71-75%, 72-72.3%, 72-75%, 72.3-75%, and the like. In some preferred embodiments of the present invention, the content of SiO2 is 68-72% or 72.5-75% by mass.

[0013] In the present invention, Bi2O3 is an important additive, and Bi2O3 can be reduced to the metallic state of bismuth, i.e., black bismuth, under a high-temperature reducing atmosphere. Based on the component design and physical and chemical treatment of the present invention, the reduction of bismuth can be locally controlled at the periphery of the effective light-transmitting area of ​​the glass, thereby reacting in situ on the glass substrate to generate a light-absorbing layer with high light-absorbing ability, which can effectively absorb stray light passing through the glass and reduce the halo effect. Since the light-absorbing layer and the light-transmitting effective area are gradual transition layers, there is no obvious interface, and the light-absorbing layer has a high absorptivity, the interface reflectivity is extremely low, which can significantly eliminate the halo and improve the accuracy and clarity of weak signal detection. In an embodiment of the present invention, the content of Bi2O3 is 0.5-1% by mass. In some embodiments of the present invention, the content of Bi2O3 is measured in mass percentage, and can also be selected from the following range or the range composed of any value in the following range or any value in the following range: 0.5-0.7%, 0.5-1%, 0.7-1%, and so on. In some preferred embodiments of the present invention, the content of Bi2O3 is 0.5-0.7% or 0.7-1% by mass.

[0014] In the present invention, Li2O and Na2O are the oxides of the glass network. Alkali metal ions are easy to move and diffuse in the glass, which can reduce the viscosity of the glass during high-temperature melting and make the glass easy to melt. They are good fluxing agents. + Chemical strengthening is also called ion exchange strengthening. Its principle is to place the glass in molten potassium nitrate at a certain temperature to make the small radius ions (such as Na +) and large radius ions in molten salts (such as K + ) are replaced, thereby producing a "squeezing" effect on the glass surface, forming a surface compressive stress layer, and improving the mechanical strength of the glass material.

[0015] In an embodiment of the present invention, the amount of Li2O is 0-5% by mass. In some embodiments of the present invention, the content of Li2O is 0-5% by mass, and can also be selected from the following ranges or any values ​​in the following ranges: 0-0.5%, 0-1%, 0-3%, 0-5%, 0.5-1%, 0.5-3%, 0.5-5%, 1-3%, 1-5%, 3-5%, 0, etc. In some preferred embodiments of the present invention, the content of Li2O is 0 or 0.5-5%, preferably 1-5%;

[0016] In an embodiment of the present invention, the amount of Na2O is 8-15% by mass percentage. In some embodiments of the present invention, the content of Na2O can also be selected from the following ranges or any values ​​in the following ranges: 8-9.3%, 8-13%, 8-15%, 9.3-13%, 9.3-15%, 13-15%, etc. In some preferred embodiments of the present invention, the amount of Na2O is 8-12.5% ​​or 13.3-5%, preferably 8-9.3% by mass percentage.

[0017] In the present invention, Al2O3 is a glass intermediate oxide, and its content affects the thermal expansion coefficient and chemical and thermal stability of the glass. Al2O3 can increase the mechanical processing performance of the glass, but too much will reduce the material properties. In addition, the volume of [AlO4] in the glass is 41cm 3 / mol, the volume of [SiO4] is 27cm 3 / mol, [AlO4] is 52% larger in volume than [SiO4], so [AlO4] will lead to an increase in the voids in the glass, which is beneficial to improving the efficiency of ion exchange and making the glass material have excellent chemical strengthening properties. Among them, "material properties" refers to a physical property of glass in a high-temperature molten state, which is distinguished by "long / short" and must be accurately detected with the help of instruments. For example, a rheometer can be used to test the viscosity of the sample in a viscoelastic state, and the rate of change of its viscosity can be calculated. The faster the change rate of the glass viscosity, the shorter the material properties become, and the slower the change rate of the glass viscosity, the longer the material properties become. In an embodiment of the present invention, the amount of Al2O3 is 10 to 15% by mass. In some embodiments of the present invention, the content of Al2O3 is calculated as a mass percentage, and can also be selected from the following ranges or a range composed of any values ​​in the following ranges or any values ​​in the following ranges: 10-11%, 10-12%, 10-13%, 10-15%, 11-12%, 11-13%, 11-15%, 12-13%, 12-15%, 13-15%, etc. In some preferred embodiments of the present invention, the content of Al2O3 is calculated as a mass percentage of 11-15%, more preferably 11-13%.

[0018] In the present invention, B2O3 is a glass-forming oxide, and B can partially replace Si in silicate glass to form a network structure. In addition, B2O3 has a fluxing effect in glass, which can reduce the high-temperature viscosity of glass, save costs, and facilitate production. However, as the content of B2O3 increases, the devitrification range of glass increases, and B2O3 is volatile and can pollute the environment, so the amount should be strictly controlled during the production process. In an embodiment of the present invention, the amount of B2O3 is 0-6% by mass percentage. In some embodiments of the present invention, the content of B2O3 is measured by mass percentage, and can also be selected from the following range or any range composed of any value in the following range or any value in the following range: 0-1%, 0-2%, 0-6%, 1-2%, 1-6%, 2-6%, 0, etc. In some preferred embodiments of the present invention, the amount of B2O3 is 1-6%, preferably 1-2% or 2-6%.

[0019] In the present invention, the addition of CaO can stabilize the glass structure and reduce its phase separation tendency, thereby improving the uniformity and stability of the glass. CaO belongs to the glass network regulator in the present invention, which can react with the silicon oxygen network formed by SiO2, and reduce the melting temperature of the glass (fluxing effect) by introducing non-network oxygen (network breaking effect). This network breaking effect does not lead to the substantial disconnection of the network, but makes it easier to adjust the morphology without destroying the overall structure of the silicon oxygen network. At the same time, the addition of CaO helps to form a polycyclic structure in the silicon oxygen network structure, such as a three-membered ring, a four-membered ring, a five-membered ring and a six-membered ring. These polycyclic structures increase the diversity and complexity of the glass network and help maintain the overall stability of the glass structure. And, by creating more gaps between network structure units, the addition of CaO creates more channels for ion exchange. In the chemical strengthening process, smaller ions (such as sodium ions) are replaced by larger ions (such as potassium ions), thereby improving the bending strength, impact resistance and drop resistance of the glass. In an embodiment of the present invention, the amount of CaO is 0.1 to 3% by mass percentage. In some embodiments of the present invention, the content of CaO is calculated as a percentage by mass, and can also be selected from the following ranges or a range composed of any values ​​in the following ranges or any values ​​in the following ranges: 0.5-1%, 0.5-1.3%, 0.5-2%, 0.5-2.5%, 0.5-3%, 1-1.3%, 1-2%, 1-2.5%, 1-3%, 1.3-2%, 1.3-2.5%, 1.3-3%, 2-2.5%, 2-3%, 2.5-3%, etc. In some preferred embodiments of the present invention, the content of CaO is calculated as a percentage by mass of 0.5-2.5%, preferably 1-2.5%, and more preferably 1.3-2.5%.

[0020] In the present invention, CeO2 and As2O3 are variable valence oxides, which are mainly used to remove bubbles from the glass liquid by being reduced at high temperature (losing oxygen) and oxidized at low temperature (obtaining oxygen). The process of decomposing and releasing oxygen at high temperature will increase the gas partial pressure in the bubbles, increase the volume of the bubbles, and thus accelerate the bubbles to rise and be removed from the molten glass. In addition, the released oxygen can also participate in the oxidation reaction in the molten glass, which helps to eliminate some impurities with strong reducing properties and improve the optical properties and chemical stability of the glass.

[0021] In an embodiment of the present invention, the amount of CeO2 is 0-1% by mass percentage. In some embodiments of the present invention, the content of CeO2 is measured by mass percentage, and can also be selected from the following ranges or the range composed of any value in the following ranges or any value in the following ranges: 0-0.2%, 0-0.6%, 0-0.7%, 0-1%, 0.2-0.6%, 0.2-0.7%, 0.2-1%, 0.6-0.7%, 0.6-1%, 0.7-1%, 0, etc. In some preferred embodiments of the present invention, the amount of CeO2 is 0 or 0.2-1%, preferably 0.2-0.7% or 0.7-1%.

[0022] In an embodiment of the present invention, the amount of As2O3 is 0.1-1% by mass. In some embodiments of the present invention, the content of As2O3, in terms of mass percentage, can also be selected from the following ranges or any ranges composed of any values ​​in the following ranges or any values ​​in the following ranges: 0.1-0.3%, 0.1-0.5%, 0.1-0.8%, 0.1-1%, 0.3-0.5%, 0.3-0.8%, 0.3-1%, 0.5-0.8%, 0.5-1%, 0.8-1%, etc. In some preferred embodiments of the present invention, the amount of As2O3, in terms of mass percentage, is 0.3-1%, preferably 0.5-1%, preferably 0.8-1% or 0.5-0.8% or 0.3-0.5%.

[0023] In some embodiments of the present invention, the present invention comprises, by mass percentage, 68-75% SiO2, 0.5-1% Bi2O3, 0 or 0.5-5% Li2O, 8-15% Na2O, 1-2% or 2-6% B2O3, 10-15% Al2O3, 0.1-3% CaO, 0 or 0.2-1% CeO2 and 0.1-1% As2O3.

[0024] In some embodiments of the present invention, the present invention comprises, by mass percentage, 68-75% SiO2, 0.5-1% Bi2O3, 0-5% Li2O, 8-15% Na2O, 1-6% B2O3, 11-15% Al2O3, 0.5-2.5% CaO, 0-0.5% or 0.7-1% CeO2 and 0.1-1% As2O3.

[0025] In some embodiments of the present invention, the glass material prepared from the glass composition of the present invention has a wide spectral range (@300-1100nm) and excellent spectral transmittance, and its spectral transmittance at 900nm can be ≥92.5%, ≥92.54%, ≥92.87%, ≥92.99%, ≥93%, ≥93.22%, or even ≥93.63%. For example, in some embodiments of the present invention, the spectral transmittance of the glass material at 900nm is 92.5-93.63%.

[0026] In some embodiments of the present invention, the glass material prepared from the glass composition of the present invention forms a light absorption layer on the glass surface after reduction treatment, and the thickness of the light absorption layer can be ≥506μm, ≥508μm, ≥517μm, ≥519μm, ≥528μm, or even ≥539μm, and the spectral transmittance of the light absorption layer at 900nm can be ≤0.18%, ≤0.17%, ≤0.15%, ≤0.14%, ≤0.13%, ≤0.12%, or even ≤0.1%. For example, in some embodiments of the present invention, the spectral transmittance of the light absorption layer of the high-strength anti-halation photoelectric glass at 900nm is 0.1-0.17%. For example, in some embodiments of the present invention, the thickness of the light absorption layer is 506-539μm.

[0027] In some embodiments of the present invention, the relaxation temperature (T s )≥650℃.

[0028] In some embodiments of the present invention, the glass material prepared from the glass composition of the present invention has a bending strength of ≥200MPa and a falling ball impact resistance of ≥1.5m (6mm glass, 60g steel ball) after chemical strengthening. In some other embodiments, the bending strength of the glass material after chemical strengthening may be further ≥206MPa, ≥209MPa, ≥217MPa, ≥220MPa, ≥224MPa; the falling ball impact resistance height may be further ≥1.55m, ≥1.62m, ≥1.68m, ≥1.77m, ≥1.8m. For example, in some embodiments of the present invention, the bending strength of the glass material after chemical strengthening is 200-224MPa. For example, in some embodiments of the present invention, the falling ball (60g steel ball) impact resistance height of 6mm glass is 1.5-1.8m.

[0029] In a second aspect of the present invention, a glass blank is provided, which is made of the glass composition described in the first aspect.

[0030] In some embodiments of the present invention, the method for preparing the glass blank comprises: mixing the raw materials, melting at 1550-1650° C., stirring, clarifying, cooling to 1350-1450° C. for forming, and annealing at 500-620° C.

[0031] In some embodiments of the present invention, the raw materials may also be selected from the following materials as needed: quartz sand, bismuth oxide (or bismuth nitrate pentahydrate), lithium carbonate, sodium carbonate (or sodium nitrate), potassium carbonate (or potassium nitrate), boric oxide (or boric acid), aluminum hydroxide (or aluminum oxide), calcium oxide (or calcium carbonate), cerium oxide and white arsenic.

[0032] In a third aspect of the present invention, a high-strength anti-halation photoelectric glass is provided, which comprises a light-transmitting effective area, wherein the glass composition of the light-transmitting effective area is the same as the glass composition described in the first aspect.

[0033] In an embodiment of the present invention, the high-strength anti-halation photoelectric glass further comprises a light absorption layer, which is located on the surface of the effective area and is obtained by performing a reduction treatment on the light-transmitting effective area.

[0034] In some embodiments of the present invention, the reduction treatment is performed in a reducing atmosphere, wherein the time of the reduction treatment is 300 to 20,000 min, the pressure is 0.01 to 0.5 MPa, and the temperature is 550 to 680° C. The reducing atmosphere is, for example, hydrogen.

[0035] In some embodiments of the present invention, the spectral transmittance of the light-transmitting effective area at 900nm is ≥92.5%. In other embodiments, the spectral transmittance of the light-transmitting effective area at 900nm can be further ≥92.54%, ≥92.87%, ≥92.99%, ≥93%, ≥93.22%, ≥93.63%. For example, in some embodiments of the present invention, the spectral transmittance of the light-transmitting effective area of ​​the high-strength anti-halation photoelectric glass at 900nm is 92.5-93.63%.

[0036] In some embodiments of the present invention, the spectral transmittance of the light absorbing layer at 900nm is ≤0.18%, and in other embodiments, the spectral transmittance of the light absorbing layer at 900nm can be further ≤0.17%, ≤0.15%, ≤0.14%, ≤0.13%, ≤0.12%, ≤0.1%. For example, in some embodiments of the present invention, the spectral transmittance of the light absorbing layer of the high-strength anti-halation photoelectric glass at 900nm is 0.1-0.17%.

[0037] In some embodiments of the present invention, the thickness of the light absorbing layer is ≥506 μm, and in other embodiments, the thickness of the light absorbing layer may be further ≥508 μm, ≥517 μm, ≥519 μm, ≥528 μm, or ≥539 μm. For example, in some embodiments of the present invention, the thickness of the light absorbing layer is 506-539 μm.

[0038] In some embodiments of the present invention, the glass sag temperature (T s )≥650℃.

[0039] In some embodiments of the present invention, the bending strength of the glass after chemical strengthening is ≥200 MPa. In other embodiments, the bending strength of the glass after chemical strengthening may be further ≥206 MPa, ≥209 MPa, ≥217 MPa, ≥220 MPa, or ≥224 MPa. For example, in some embodiments of the present invention, the bending strength of the glass after chemical strengthening is 200-224 MPa.

[0040] In some embodiments of the present invention, the impact height of a 6mm glass against a falling ball (60g steel ball) is ≥1.5m, and in some other embodiments, the impact height may be further ≥1.55m, ≥1.62m, ≥1.68m, ≥1.77m, ≥1.8m. For example, in some embodiments of the present invention, the impact height of a 6mm glass against a falling ball (60g steel ball) is 1.5 to 1.8m.

[0041] In some embodiments of the present invention, the chemical strengthening comprises placing the glass including the light absorbing layer in molten salt, and the temperature of the chemical strengthening is 380 to 480° C. and the time is 30 to 600 min.

[0042] In some embodiments of the present invention, the molten salt is selected from a mixed molten salt of one or more of lithium salt, sodium salt and potassium salt.

[0043] In a fourth aspect of the present invention, a method for preparing the high-strength anti-halation photoelectric glass according to the third aspect is provided, comprising: mixing raw materials, melting at 1550-1650° C., stirring, clarifying, cooling to 1350-1450° C. for forming, and annealing at 500-620° C. to obtain a glass blank;

[0044] The glass blank is precisely processed and then subjected to reduction treatment to form a light absorbing layer on the glass surface;

[0045] The glass with a light absorption layer on the surface is mechanically processed and then chemically strengthened to obtain high-strength anti-halation photoelectric glass.

[0046] In an embodiment of the present invention, the goal of the precision machining is to produce parts with precise size, tolerance or surface roughness, and appropriate operations can be selected according to the needs. For example, in one embodiment of the present invention, glass is processed into a glass frustum or step-shaped glass of a certain size by precision machining. The precision machining of the present invention may include, for example, milling, turning, drilling and grinding. For example, in some embodiments of the present invention, glass blanks are rounded, rolled, sliced ​​and stepped to obtain step-shaped glass.

[0047] In an embodiment of the present invention, mechanical processing includes grinding, polishing, carving, chamfering, etc. For example, in one embodiment of the present invention, the upper and lower surfaces of a glass cone or a step-shaped glass with a light absorption layer formed on the surface are mechanically processed to ensure that the parallelism of the upper and lower circular surfaces is ≤0.01mm, the coaxiality is ≤0.02mm and the surface roughness is ≤10nm.

[0048] In some embodiments of the present invention, the reduction treatment is performed in a reducing atmosphere, wherein the reduction treatment time is 300 to 20,000 min, the pressure is 0.01 to 0.5 MPa, and the temperature is 550 to 680°C.

[0049] In some embodiments of the present invention, the chemical strengthening comprises placing the glass including the light absorbing layer in molten salt, and the temperature of the chemical strengthening is 380 to 480° C. and the time is 30 to 600 min.

[0050] In some embodiments of the present invention, the molten salt is selected from a mixed molten salt of one or more of lithium salt, sodium salt and potassium salt.

[0051] In a fifth aspect of the present invention, an optical element is provided, which is made of the glass composition described in the first aspect or the glass blank described in the second aspect, or includes the anti-halation photoelectric glass described in the third aspect.

[0052] In some embodiments of the present invention, the optical element is an optical input window.

[0053] In a sixth aspect of the present invention, a low-light level image intensifier is provided, comprising the optical element described in the fifth aspect. In some embodiments of the present invention, the optical element is an optical input window.

[0054] In the seventh aspect of the present invention, there is provided the application of the glass composition described in the first aspect, or the glass blank described in the second aspect, or the high-strength anti-halation photoelectric glass described in the third aspect, or the optical element described in the fifth aspect, or the low-light image intensifier described in the sixth aspect in the field of photoelectric detection and precision optics.

[0055] In some embodiments of the present invention, the application is as an optical input window of an optical system or a photoelectric detection system.

[0056] In some embodiments of the present invention, the application is as an optical input window in a low-light night vision device, an ultraviolet detection device, a space measurement and control device, an information display device, an industrial camera or a high-end lens.

[0057] In some embodiments of the present invention, the application is for preparing an optical input window of a low-light level image intensifier.

[0058] The specific technical features described in all the embodiments of the various aspects of the present invention can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further explain various possible combinations.

[0059] Unless otherwise specified, the numerical range described in the present invention includes all the values ​​within this range, and includes the range values ​​composed of any two values ​​within this range. For example, 0-0.5%, this numerical range includes all the values ​​between 0 and 0.5, and includes the range values ​​composed of any values ​​within this range (for example: 0.01%, 0.2%, 0.49%) (for example, 0.01-0.49%, 0.01-0.2%, 0.2-0.49%). Different numerical values ​​of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value.

[0060] Through one or more of the above technical means, the following beneficial effects can be achieved:

[0061] The present invention provides a glass composition and a high-strength anti-halation photoelectric glass material prepared from the glass composition. The glass material having the glass composition of the present invention or the high-strength anti-halation photoelectric glass material of the present invention has a wide spectral range (@300-1100nm), excellent spectral transmittance, effective area spectral transmittance ≥ 92.5% @ 900nm, excellent stray light elimination and crosstalk prevention performance after high-temperature reduction treatment, light absorption layer transmittance ≤ 0.18% @ 900nm, high baking resistance temperature, glass sag temperature (T s )≥650℃, after chemical strengthening, it has high bending strength, good impact resistance, bending strength ≥200MPa, and ball impact resistance ≥1.5m. It can be used to prepare optical input windows of optical systems and photoelectric detection systems, and has broad application prospects in photoelectric detection and precision optics fields such as low-light night vision, ultraviolet detection, space measurement and control, information display, industrial cameras, and high-end lenses. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] The drawings constituting part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. The implementation scheme of the present application is described in detail below in conjunction with the drawings, wherein:

[0063] Figure 1 A comparison chart of the transmittance (@900nm) of the effective area and the absorption layer before and after the glass reduction treatment of Examples 1 to 6 of the present invention and Comparative Examples 1 to 4 is shown.

[0064] Figure 2 A schematic structural diagram of a step-type glass is shown.

[0065] Figure 3 A numerical comparison chart of the sag temperature and the bending strength after chemical strengthening of the glass materials of Examples 1 to 6 of the present invention and Comparative Examples 1 to 4 is shown. DETAILED DESCRIPTION

[0066] The present application is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0067] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in this application can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in this application are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the content described herein can be applied to the method of this application. The preferred implementation methods and materials described in the text are for demonstration purposes only.

[0068] The sag temperature (T) of glass samples was measured using the NETZSCH DIL 402 expansion coefficient tester. s ), the sag temperature refers to the temperature at which the glass sample stops expanding during heating. Sample preparation: The glass sample is polished into a cylindrical glass strip of Φ6×50mm, and the two end surfaces are parallel. The heating rate is set to 5℃ / min, and the data acquisition cycle is 20ms. The data is plotted as a curve of the relationship between temperature and linear expansion, and the glass sag temperature (T) is obtained by the tangent method. s ). (GB / T7962.16~2010)

[0069] Use Shimadzu UV-Vis spectrophotometer (UV~3600Plus) to test the transmittance. Sample preparation: the sample should be larger than the effective aperture of the light port, 2mm thick, and double-sided polished. During the test, input the wavelength range, scanning speed and other parameters to test the sample transmittance. (GB / T 7962.12-2010)

[0070] The bending strength of the glass sample is measured using a three-point bending tester. The sample size is 3mm×4mm×40mm. The four long sides of the tested glass sample are optically polished, the long edges are chamfered, and the end surface of the test sample does not require special treatment. (GB / T 6569-2006)

[0071] The impact resistance test was conducted using the MK-9968 2000mm drop ball impact tester produced by Dongguan Kemai Instruments Co., Ltd. The steel ball mass was specified to be 60g. Sample preparation: The glass sample was ground and polished into a Φ30×6mm frustum, and the two end surfaces were kept parallel. (GB / T 39814-2021)

[0072] The invention provides a high-strength anti-halation photoelectric glass material. The glass material comprises, by mass percentage, 68-75% of SiO2, 0.5-1% of Bi2O3, 0-5% of Li2O, 8-15% of Na2O, 0-6% of B2O3, 10-15% of Al2O3, 0.1-3% of CaO, 0-1% of CeO2 and 0.1-1% of As2O3.

[0073] In particular, when the glass material of the present invention is composed of the above components, in some embodiments of the present invention, the glass material of the present invention has excellent spectral transmittance, the spectral transmittance in the effective area is ≥92.5%@900nm, and after high-temperature reduction treatment, it has excellent stray light elimination and crosstalk prevention performance, the transmittance of the light absorption layer is ≤0.18%@900nm, and has a high baking resistance temperature, and the glass sag temperature (T s )≥650℃, and has high bending strength and good impact resistance after chemical strengthening, with bending strength ≥200MPa and falling ball impact resistance ≥1.5m. It can be used to prepare optical input windows of optical systems and photoelectric detection systems, including but not limited to low-light night vision, ultraviolet detection, space measurement and control, information display, industrial cameras, high-end lenses and other fields.

[0074] Furthermore, the present invention provides a method for preparing a high-strength anti-halation photoelectric glass material, comprising: mixing various glass raw materials in proportion, melting the batch materials at a high temperature of 1550-1650°C, mechanically stirring, assisting bubbling clarification, then cooling to 1350-1450°C and forming by mechanical or manual casting, and annealing at 500-620°C after forming to obtain the photoelectric glass blank.

[0075] The glass blank is processed into a glass truncated cone or stepped glass of a certain size by precision machining; the glass truncated cone or stepped glass is subjected to reduction treatment under specific time, pressure and temperature conditions to form a light absorption layer on the glass surface. The reduction treatment time is 300 to 20,000 minutes, the pressure is 0.01 to 0.5 MPa, and the temperature is 550 to 680°C. For example, the glass blank can be rounded, rolled, sliced ​​and stepped to obtain a stepped glass.

[0076] The upper and lower surfaces of the glass frustum or stepped glass with a light absorption layer formed on the surface are machined to ensure that the parallelism of the upper and lower circular surfaces or the upper and lower surfaces is ≤0.01mm, the coaxiality is ≤0.02mm and the surface roughness is ≤10nm, the light absorption layer on the upper and lower surfaces is removed, and the light absorption layer on the remaining surfaces is retained.

[0077] The processed glass is chemically strengthened to obtain the high-strength anti-halation photoelectric glass material. The chemical strengthening is carried out in molten salt at a temperature of 380 to 480° C. for 30 to 600 minutes. The molten salt is selected from a mixed molten salt of one or more of lithium salt, sodium salt and potassium salt.

[0078] The method of the present invention has process stability, and the glass material prepared by the process method can show stable characteristics, and will not cause significant fluctuations in glass performance due to the increase or decrease of the process within the range. Of course, it is understandable that within the process range, some higher temperatures can shorten the preparation process compared to lower temperatures. If it is necessary to shorten the time cost as much as possible, those skilled in the art can choose a relatively higher temperature within the temperature range disclosed in the present invention when operating.

[0079] Specifically, the embodiments and comparative examples of the present invention are carried out according to the above method, wherein the compositions of the glass samples of embodiments 1 to 6 and comparative examples 1 to 4 are shown in Table 1.

[0080] The preparation process parameters of the glass samples of Examples 1 to 6 of the present invention are shown in Table 2, wherein the process parameters of Comparative Examples 1 to 4 are the same as those of Example 6.

[0081] The reducing atmosphere of the reduction treatment is hydrogen, the reducing time is 10000 min, the reducing temperature is 620°C, and the reducing atmosphere pressure is 0.05 MPa. The molten salt used in the chemical strengthening treatment is molten potassium nitrate, the chemical strengthening temperature is 440°C, and the chemical strengthening time is 180 min. The glass morphology prepared in Examples 1 to 6 and Comparative Examples 1 to 4 is a step-type, and its structural schematic diagram is shown in FIG. Figure 3 shown.

[0082] The properties of the glass samples of Examples 1 to 6 of the present invention and Comparative Examples 1 to 4 are shown in Table 3.

[0083] Table 1 Composition of glass samples of Examples 1 to 6 and Comparative Examples 1 to 4

[0084]

[0085]

[0086] Table 2 Glass sample preparation process of Examples 1 to 6

[0087]

[0088] Table 3 Performance test results of glass samples of Examples 1 to 6 and Comparative Examples 1 to 4

[0089]

[0090]

[0091] As shown in Table 3, the high-strength anti-halation photoelectric glass material of each embodiment has excellent spectral transmittance, a wide spectral range (@300~1100nm), an effective area spectral transmittance ≥92.5%@900nm, excellent stray light elimination and crosstalk prevention performance after high-temperature reduction treatment, a light absorption layer transmittance ≤0.18%@900nm, a high baking resistance temperature, and a glass sag temperature (T s )≥650℃, after chemical strengthening, it has higher flexural strength, better impact resistance, flexural strength ≥200MPa, and ball impact resistance ≥1.5m.

[0092] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. Although the present application is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A high-strength anti-halation photoelectric glass, comprising a light-transmitting effective area and a light-absorbing layer, wherein: The light absorption layer is located on the surface of the light transmission effective area and is obtained by performing a reduction treatment on the light transmission effective area; The glass composition of the light-transmitting effective area, in terms of mass percentage, consists of the following components: 68~75% SiO2, 0.5~1% Bi2O3, 0~5% Li2O, 8~15% Na2O, 2~6% B2O3, 10~15% Al2O3, 0.1~3% CaO, 0.2~1% CeO2 and 0.1~1% As2O3.

2. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the SiO2 content is 68~72%.

3. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the SiO2 content is 72.5~75%.

4. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of Bi2O3 is 0.5~0.7%.

5. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of Bi2O3 is 0.7~1%.

6. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of Li2O is 0.

7. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of Li2O is 0.5~5%.

8. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of Li2O is 1~5%.

9. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of Na2O is 8~12.5%.

10. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of Na2O is 5-13.3%.

11. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of Na2O is 8~9.3%.

12. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of Al2O3 is 11~15%.

13. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of Al2O3 is 11~13%.

14. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the CaO content is 0.5~2.5%.

15. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the CaO content is 1~2.5%.

16. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the CaO content is 1.3~2.5%.

17. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of CeO2 is 0.2~0.7%.

18. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of CeO2 is 0.7~1%.

19. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of As2O3 is 0.3~1%.

20. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of As2O3 is 0.5~1%.

21. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of As2O3 is 0.8~1%.

22. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of As2O3 is 0.5~0.8%.

23. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, the content of As2O3 is 0.3~0.5%.

24. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: In terms of mass percentage, it consists of the following components: 68~75% SiO2, 0.5~1% Bi2O3, 0~5% Li2O, 8~15% Na2O, 2~6% B2O3, 11~15% Al2O3, 0.5~2.5% CaO, 0.7~1% CeO2 and 0.1~1% As2O3.

25. The high-strength anti-halation photoelectric glass according to claim 1, characterized in that: The reduction treatment is carried out in a reducing atmosphere, wherein the time of the reduction treatment is 300-20000 min, the pressure is 0.01-0.5 MPa, and the temperature is 550-680°C.

26. The high-strength anti-halation photoelectric glass according to any one of claims 1 to 25, characterized in that: The spectral transmittance of the effective light transmission area at 900nm is ≥92.5%; The spectral transmittance of the light absorption layer at 900nm is ≤0.18%; Glass sag temperature ≥ 650 ℃; The bending strength of chemically strengthened glass is ≥200 MPa and the impact resistance of falling ball is ≥1.5 m.

27. The high-strength anti-halation photoelectric glass according to claim 26, characterized in that: The chemical strengthening comprises placing the glass including the light absorbing layer in molten salt, the temperature of the chemical strengthening is 380-480° C., and the time is 30-600 min.

28. The high-strength anti-halation photoelectric glass according to claim 27, characterized in that: The molten salt is selected from a mixed molten salt of one or more of lithium salt, sodium salt and potassium salt.

29. A method for preparing the high-strength anti-halation photoelectric glass according to any one of claims 1 to 28, comprising: The raw materials are mixed, melted at 1550-1650°C, stirred, clarified, cooled to 1350-1450°C for forming, and annealed at 500-620°C to obtain a glass blank; The glass blank is precisely processed and then subjected to reduction treatment to form a light absorbing layer on the glass surface; The glass with a light absorption layer on the surface is mechanically processed and then chemically strengthened to obtain high-strength anti-halation photoelectric glass.

30. The method according to claim 29, characterized in that The reduction treatment is carried out in a reducing atmosphere, wherein the time of the reduction treatment is 300-20000 min, the pressure is 0.01-0.5 MPa, and the temperature is 550-680°C.

31. The method according to claim 29, characterized in that The chemical strengthening comprises placing the glass including the light absorbing layer in molten salt, the temperature of the chemical strengthening is 380-480° C., and the time is 30-600 min.

32. The method according to claim 31, characterized in that The molten salt is selected from a mixed molten salt of one or more of lithium salt, sodium salt and potassium salt.

33. An optical element comprising the high-strength anti-halation photoelectric glass according to any one of claims 1 to 28.

34. The optical element according to claim 33, characterized in that The optical element is an optical input window.

35. A low-light image intensifier, characterized in that: The low-light level image intensifier comprises the optical element described in claim 33 or 34.

36. The low-light level image intensifier according to claim 35, characterized in that: The optical element is an optical input window.

37. Application of the high-strength anti-halation photoelectric glass according to any one of claims 1 to 28, or the optical element according to claim 33 or 34, or the low-light image intensifier according to claim 35 or 36 in the field of photoelectric detection and precision optics.

38. The use according to claim 37, characterized in that The application is as an optical input window for an optical system or a photoelectric detection system.

39. The use according to claim 37, characterized in that The application is as an optical input window in low-light-level night vision equipment, ultraviolet detection equipment, space measurement and control equipment, information display equipment, industrial cameras or high-end lenses.

40. The use according to claim 37, characterized in that The application is to prepare an optical input window for a low-light level image intensifier.

Citation Information

Patent Citations

  • Manufacturing method of optical cover plate, optical cover plate and wearable device

    CN113437181A

  • Glass for press molding and glass substrate for information recording medium

    JP2002167230A